Religious outsiders and the making of Americans - Moore, R. Laurence (Robert Laurence), 1940- (Oxford : Oxford University Press, 1986)
In light of the curious compulsion to stress Protestant dominance in America's past, this book takes an unorthodox look at religious history in America. Rather than focusing on the usual mainstream Protestant churches--Episcopal, Congregationalist, Methodist, Baptist, and Lutheran--Moore instead turns his attention to the equally important "outsiders" in the American religious experience and tests the realities of American religious pluralism against their history in America. Through separate but interrelated chapters on seven influential groups of "outsiders"--The Mormons, Catholics, Jews, Christian Scientists, Millennialists, 20th-century Protestant Fundamentalists, and the African-American churches--Moore shows that what was going on in mainstream churches may not have been the "normal" religious experience at all, and that many of these "outside" groups embodied values that were, in fact, quintessentially American.